Service aware base station processing resource allocation for centralized radio access network - Xinping ZHANG; Yuanyuan WANG; Lin TIAN; Shuliang HAO (Dianxin kexue)
Current research on resource allocation algorithmsmainly focuses on data centers,and cloud computing environments.These resource allocation algorithms did not consideRthe diversity of processing resources(CPU,memory,network bandwidth,FPGA,DSP)and the diversity of service types in the centralized base station,resulting in the low processing resource utilization.In ordeRto solve this problem,a service oriented base station processing resource allocation algorithm was proposed.Firstly,the Fisher partitionmethod was used to classify the base station’s processing resource requirements according to the user’s service request.Then,the resource allocation balancing strategy was used to allocate the base station processing resources.Experimental results show that the algorithm is effective to reduce the number of physi cal servers and improves the resource utilization of the servers,realizing energy conservation and communications.